One-dimensional vs. two-dimensional proton transport processes at solid–liquid zinc-oxide–water interfaces. Issue 4 (20th November 2018) - Hellström, Matti; Quaranta, Vanessa; Behler, Jörg
Abstract : Neural network molecular dynamics simulations unravel the long-range proton transport properties of ZnO–water interfaces. Abstract : Long-range charge transport is important for many applications like batteries, fuel cells, sensors, and catalysis. Obtaining microscopic insights into the atomistic mechanism is challenging, in particular if the underlying processes involve protons as the charge carriers. Here, large-scale reactive molecular dynamics simulations employing an efficient density-functional-theory-based neural network potential are used to unravel long-range proton transport mechanisms at solid–liquid interfaces, using the zinc oxide–water interface as a prototypical case. We find that the two most frequently occurring ZnO surface facets, (101̄0) and (112̄0), that typically dominate the morphologies of zinc oxide nanowires and nanoparticles, show markedly different proton conduction behaviors along the surface with respect to the number of possible proton transfer mechanisms, the role of the solvent for long-range proton migration, as well as the proton transport dimensionality. Understanding such surface-facet-specific mechanisms is crucial for an informed bottom-up approach for the functionalization and application of advanced oxide materials.